Reconstructing historic Labrador Inuit plant use: an exploratory phytolith analysis of soapstone-vessel residues - Pigford, Ashlee Ann; Zutter, Cynthia (My University, 2014)
Phytoliths (microscopic silica plant remains) found in a variety of archaeological contexts offer insight into reconstructing past ecology and human behavior. We present an exploratory phytolith study on residues from soapstone fragments retrieved from the 18th-century Labrador Inuit winter site Dog Island-Oakes Bay I, Labrador (HeCg-08). Phytoliths were extracted from residues and identified using a phytolith reference collection developed from ten contemporary Labrador plants and two European imports. Recovered phytoliths suggest that imported cereals (Avena sp., Secale sp.), local edible berries, medicinal and tea plants (Empetrum nigrum, Epilobium latifolium, Ledum decumbens, Salix sp., Picea sp., Rubus chamaemorus, and Vaccinium sp.) were present in the residues. Our findings supplement recent palaeoethnobotanical research that suggests plants may have played a role in the subsistence practices of 18th-century Labrador Inuit. As a pioneering effort in the archaeology of Labrador Inuit, the successful recovery of phytoliths from our study encourages further phytolith investigations in this region.
Keywords: phytoliths; Inuit